COATING OF SPHERES AND TUBES WITH AEROGELS - BIENER, JUERGEN; WALTON, CHRISTOPHER, C; KIM, SUNG HO; WORSLEY, MARCUS, A; DAWEDEIT, CHRISTOPH; HAMZA, ALEX, V; SATCHER, JOE; WU, KUANG JEN (2013)
A method for preparing aerogel coatings in the interior surface of a tube or sphere using a device simulating a microgravity environment is described. The method includes forming a reaction mixture in the container of a first monomer and a solvent; rotating the container to simulate a microgravity environment in the container's interior, under conditions sufficient to form a wet gel coating the container's interior surface; and contacting the wet gel with supercritical carbon dioxide under conditions suitable to form the aerogel, thereby forming the aerogel coating. La présente invention porte sur un procédé de préparation de revêtements d'aérogel dans la surface intérieure d'un tube ou d'une sphère à l'aide d'un dispositif simulant un environnement de microgravité.